New Method of Estimation of the Speed of Light in Vacuum Using Q-Values of Beta-Décay-Transitions in Mirrors Nuclei - Sakho, Ibrahima (Schrödinger: Journal of Physics Education, 2025)
Purpose of the study: The goal of this work is to present a new method named Q-b-decay theory to estimate the speed of light. Our result is compared with the earlier estimations since the first measurement of Roemer in 1676 up to 2022, the latter being measured experimentally by picosecond laser technology. Methodology: This research is based on an estimation of the speed of light in vaccum. This speed is expressed in terms of the Q-value of b+- decay transitions in mirrors nuclei in the framework of the nuclear model with a nucleon constant density. The speed of light is calculated using the experimental Q-values of 37K and 65As miroirs nuclei. Main Findings: The research gives the result c = 299 791 777 m/s agreeing excellently with the exact value 299 792 458 m/s with an accuracy at 0.000 23 %. This result shows that the speed c of light is obtained accurately from nuclear properties instead of light properties or electric and magnetic constants. A useful appendix for students details the methods of Roemer, Bradley, Fizeau, and Foucault along with the equations allowing one to calculate the speed of light they found. Novelty/Originality of this study: Estimating the speed c of light with a high accuracy using a new method based on the properties of b+- decay transitions in mirrors nuclei. As far as we know, it the first time that the speed of light is accurately estimated via a non-optical method 348 years ago since 1676.